2020
DOI: 10.1017/inp.2020.29
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Ventenata dubia 30 years postinvasion to bunchgrass communities in the Pacific Northwest

Abstract: Ventenata dubia (Leers) Coss., an invasive winter annual grass, negatively impacts grassland community composition and function in the Pacific Northwest. Ventenata dubia established in Palouse prairie and canyon grasslands of northern Idaho/eastern Washington in the mid-1980s to early 1990s. Understanding and comparing patterns of invasion can elucidate future trends as its range expands. We performed surveys in Palouse prairie (2012 and 2013) and canyon grasslands (2018) to assess V. dubia abundance. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
0
17
1
Order By: Relevance
“…Because V. dubia invasion has been documented lowering species diversity (Jones et al 2018(Jones et al , 2020Novak et al 2015), we hypothesized some increase of species diversity with V. dubia control. Although removal of V. dubia resulted in large changes in cover for some species, such as P. smithii, we did not find a change in species richness 1 yr after treatment as a result of V. dubia removal in either study (P > 0.18; Table 4).…”
Section: Studymentioning
confidence: 97%
See 1 more Smart Citation
“…Because V. dubia invasion has been documented lowering species diversity (Jones et al 2018(Jones et al , 2020Novak et al 2015), we hypothesized some increase of species diversity with V. dubia control. Although removal of V. dubia resulted in large changes in cover for some species, such as P. smithii, we did not find a change in species richness 1 yr after treatment as a result of V. dubia removal in either study (P > 0.18; Table 4).…”
Section: Studymentioning
confidence: 97%
“…Ventenata dubia can reduce biodiversity of areas it invades (Jones et al 2018(Jones et al , 2020 and has negative impacts on wildlife and its habitat, namely birds, through trophic cascades (Mackey 2014). Similar to other invasive species, species richness and diversity were negatively correlated with increasing V. dubia cover (Jones et al 2018(Jones et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Forb cover decreased over time as the cover of Ventenata dubia increased, adding evidence to showing negative impacts of invasive TA B L E 5 Relationships between Ventenata dubia and forb cover (%), species richness, and diversity for sampling years separately, and combined with simple linear regressions annual grasses (Melgoza et al, 1990;D'Antonio & Vitousek, 1992;Knapp, 1996;Ogle et al, 2003;Davies, 2011;McGranahan et al, 2012;Endress et al, 2019) including a decrease in native species richness (Ashton, et al, 2016;Jones et al, 2020). This supports the findings of Averett et al (2020), who also reported a decrease in native perennial forb cover from 2008 to 2016 on the PNB in different experimental sites from our study.…”
Section: Forb Response To Increasing Ventenata Dubiamentioning
confidence: 99%
“…In some situations, timing of hay harvest schedules had to be altered to avoid export losses due to V. dubia (Wallace et al 2015). V. dubia has been associated with a decrease in plant species richness and diversity in the Palouse prairie and Canyon lands (Jones et al 2020), and a decline in nesting success of insect-eating birds due to a loss of biodiversity in conservation lands in northern Idaho (Jones et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since this species is still relatively new to the region, little information has been published about its habitat niche and distribution potential. In the Paci c Northwest it was rst observed in wetter sites but has spread to drier habitats over the last 30 years (Jones et al 2020). Species distribution modeling (SDM) is a well-established technique to evaluate climate and environmental requirements of a species, and project the potential habitat range for the species of interest.…”
Section: Introductionmentioning
confidence: 99%